The usage of Foodpanda delivery apps among students: an exploratory study / Mohd Najmie Osman, Norhidayah Ali and Azyyati Anuar - Osman, Mohd Najmie; Ali, Norhidayah; Anuar, Azyyati (Universiti Teknologi MARA, Perlis, 2024)
Within the food and beverage industry in Malaysia, food delivery service, particularly the application of food delivery apps, is an emerging new wave. The escalation of food delivery apps could shift consumer behaviour in the purchase of food. The paper aims to explore contributing factors influencing consumer behaviour using food delivery apps using a qualitative approach. The approach entails the use of semistructured interviews with eight students, all of whom are Foodpanda food delivery app users, in a high-learning institution. Thematic method of data analysis revealed the following factors influencing the app usage behaviour: Ease of use, Variety of Choice, Social effect, and Time/Cost saving. This finding highlights the behavioural pattern of food delivery app users, which informs on better marketing strategies and planning for future business opportunities.